New Sesquiterpenoids From Plant-Associated Irpex lacteus - Luo, Huai-Zhi; Jiang, Huan; Huang, Xi-Shan; Jia, Ai-Qun (Frontiers in Chemistry, 2022)
Bacteria produce a large number of virulence factors through the quorum sensing (QS) mechanism. Inhibiting such QS system of the pathogens without disturbing their growth is a potential strategy to control multi-drug resistant pathogens. To accomplish this, two new tremulane-type sesquiterpenoids, irpexolaceus H (1) and I (2), along with two known furan compounds, irpexlacte B (3) and C (4) were isolated from Orychophragmus violaceus (L.) O.E. Schulz endophytic fungus Irpex lacteus (Fr.) Fr. Their structures were elucidated by detailed spectroscopic data (NMR, HRESIMS, IR, UV), single-crystal X-ray diffraction, and Electronic circular dichroism (ECD) analysis. Further, those compounds were evaluated for anti-quorum sensing (anti-QS) activity, and compound 3 was found to the potential QS inhibitory activity.